PEMANFAATAN MESIN FEEDER SEBAGAI INOVASI EFISIENSI PROSES PEWARNAAN BATIK DALAM UPAYA PENINGKATAN KUALITAS PRODUK - Sunarjo, Wenti Ayu; Dwi Edi Wibowo; Nur Baiti Nasution; Nauval Rabbani; Aditya Dimas Wahyu Sasongko; Mukhamad Adzar; Evi Latifah; Rachmawati; Mulyanto; Ubaidillah; Sarah Rum Handayani; Siti Nurlaela (Jurnal Berdaya Mandiri, 2024)
Batik is a product that has become Indonesia's cultural identity. As a batik city, Pekalongan continues to strive to improve the quality of batik products so that Indonesian batik does not become extinct. One of the things that makes batik attractive is its motifs and colors. Through its appeal, batik will increasingly exist and become global. In line with the problems that exist in the batik industry, namely the problem of production time efficiency, this community service aims to provide solutions to problems in the batik industry in order to save or reduce production time, especially in the batik industry. color dyeing stage, while maintaining the quality of the batik. The dyeing process carried out by the batik industry which is the activity partner, namely Perkumpulan Kampoeng Batik Kauman and Kampung Wisata Batik Pesindon, still uses traditional dyeing techniques, so that through a batik dyeing machine solution called a feeder machine, the batik production process at the dyeing stage can be made easier. The results of this service activity were achieved with evidence of a success rate based on evaluation results reaching 87.4% as a dyeing tool innovation that had an impact on efficiency and with a color dyeing printing time of around 20-30 minutes on one 2x1m sheet of paper. cloth. Furthermore, the results of using the feeder machine are visible in the even coloring results and the batik wax does not break. This means that apart from being an efficiency solution, the feeder machine also improves the quality of batik.